Incomplete Kawasaki Disease Associated with Complicated Streptococcus pyogenes Pneumonia: A Case Report - Timothy Ronan Leahy; Eyal Cohen; Upton D Allen (Canadian Journal of Infectious Diseases and Medical Microbiology)
A three-year-old boy presented with community-acquired pneumonia complicated by empyema. Streptococcus pyogenes (group A streptococcus) was identified on culture of the pleural fluid. The patient improved with antibiotic therapy and drainage of the empyema.